The non-profit news effect: a thesis on the changing dynamics of newsroom culture at an online web outlet - Fry, Robert G., III, author; Plaisance, Patrick, advisor; Landers, James, committee member; Feller, Rich, committee member (Colorado State University. Libraries, 2015)
As the media landscape continues to undergo changes, this study examined the decision making process, culture, business model and values of a non-profit media outlet and how those areas might differ from a traditional for-profit media outlet. Patterned after Herbert J. Gans’ ethnography that was the basis for his 1979 book Deciding What’s News, the observational study lasted the course of five weeks and featured extensive interviews with key decision makers and other employees from the non-profit outlet. The non-profit outlet was part of a larger non-profit media corporation, which allowed greater opportunity for collaboration – specifically internal collaboration in what was a unique setting. Findings revealed that journalists continue to rely on a great deal of independence in the decision making process and that collaboration of print, television and radio outlets coming together could be a successful model for the future.